ANALYSIS OF THE LOW MOTIVATION OF CLASS II PRIMARY SCHOOL STUDENTS IN LEARNING - Fadhilah, Farah; Triyogo, Agus (Lingustic, Literature and English Education, 2023)
The aim of this research is to determine the low learning motivation of class II students in the process of learning activities at SD Negeri 33 Lubuklinggau. The type of this research is descriptive qualitative. The subjects in this research were all 21 class II students. The method used in this research is data collection in the form of observation, questionnaires and documentation. The results of this research show that there are still class II students who have low motivation in studying at SD Negeri 33 Lubuklinggau as seen from the results of student questionnaire responses regarding motivation in learning activities in class.